Variations of the extrapsoas course of the lumbar plexus with implications for the lateral transpsoas approach to the lumbar spine: a cadaveric study - Benes, Michal; Zido, Michal; Machac, Petr; Kaiser, Radek; Khadanovich, Anhelina; Nemcova, Simona; Kunc, Vojtech; Kachlik, David (Acta neurochirurgica, 2024)
BACKGROUND: Together with an increased interest in minimally invasive lateral transpsoas approach to the lumbar spine goes a demand for detailed anatomical descriptions of the lumbar plexus. Although definitions of safe zones and essential descriptions of topographical anatomy have been presented in several studies, the existing literature expects standard appearance of the neural structures. Therefore, the aim of this study was to investigate the variability of the extrapsoas portion of the lumbar plexus in regard to the lateral transpsoas approach. METHODS: A total of 260 lumbar regions from embalmed cadavers were utilized in this study. The specimens were dissected as per protocol and all nerves from the lumbar plexus were morphologically evaluated. RESULTS: The most common variation of the iliohypogastric and ilioinguinal nerves was fusion of these two nerves (9.6%). Nearly in the half of the cases (48.1%) the genitofemoral nerve left the psoas major muscle already divided into the femoral and genital branches. The lateral femoral cutaneous nerve was the least variable one as it resembled its normal morphology in 95.0% of cases. Regarding the variant origins of the femoral nerve, there was a low formation outside the psoas major muscle in 3.8% of cases. The obturator nerve was not variable at its emergence point but frequently branched (40.4%) before entering the obturator canal. In addition to the proper femoral and obturator nerves, accessory nerves were present in 12.3% and 9.2% of cases, respectively. CONCLUSION: Nerves of the lumbar plexus frequently show atypical anatomy outside the psoas major muscle. The presented study provides a compendious information source of the possibly encountered neural variations during retroperitoneal access to different segments of the lumbar spine.
Keywords: senioři; mrtvola; Cadaver; bederní obratle; Ilioinguinal nerve; Lumbar plexus; Lateral transpsoas approach; Minimally Invasive Surgical Procedures; nervus femoralis; mužské pohlaví; bederní svaly; Genitofemoral nerve; Psoas Muscles; Iliohypogastric nerve; Lateral femoral cutaneous nerve; Femoral nerve; ženské pohlaví; Humans; Obturator Nerve; nervus obturatorius; Lumbosacral Plexus; plexus lumbosacralis; miniinvazivní chirurgické výkony; Female; Lumbar Vertebrae; Aged; Femoral Nerve; lidé; Male; Obturator nerve